Peran Orang Tua dalam Mencegah Keterlambatan Perkembangan Motorik Kasar dan Halus pada Anak Usia Dini - Intan Furqani Husna; Ismaniar Ismaniar; Lili Dasa Putri (Jurnal Pendidikan Sosial Dan Konseling, 2025)
Gross and fine motor development are crucial aspects that determine children’s readiness to learn, interact, and adapt to their surroundings. Delays in these areas affect independence, self-confidence, and social skills. This descriptive study aims to provide an in-depth overview of the parental role in preventing motor development delays through proper stimulation, supportive parenting, and cross-sector collaboration. The study used a qualitative descriptive method based on literature review and simple field observation. The findings reveal that nutrition, insufficient stimulation, and overprotective parenting are the main causes of motor delays. Parents play a key role as primary facilitators in shaping children’s physical habits and providing meaningful learning experiences. Planned stimulation, safe exploration spaces, and active involvement in daily activities significantly contribute to optimal motor development. Collaboration among families, educators, and health workers is essential for sustainable prevention efforts.